Increasing Changes to the Training Curriculum on Data Processing and Analysis Practices for Scientific Writing Training Participants - Kamaliah, Naily; Muhajarah, Kurnia; Rahman, Alpha Fadila Juliana (IJECA (International Journal of Education and Curriculum Application), 2023)
Publication of Scientific Writing in national scientific journals is a demand that must be fulfilled as a form of scientific responsibility, and has an impact on increasing interest in Scientific Writing Training. Data processing and analysis is one of the materials that is considered important in Scientific Writing training. However, in reality, this material is not easy to convey to participants. The power of data processing and analysis material is not only theoretical, but also needs to be deepened through the practice of data processing and analysis. This research aims to evaluate the effectiveness of curriculum changes in Basic Level of Scientific Writing training which focuses on Data Processing and Analysis Practices material, by comparing the evaluation results in 2022 and 2023. The instruments used in this research are (1) evaluation assessment of training implementation from participants for training organizers, as well as (2) Scientific Writing Seminar assessments, with respondents of 105 Scientific Writing Training participants in 2022, and 126 Scientific Writing training participants in 2023. Data analysis processing was carried out using Boxplot descriptive statistical analysis and continued with inferential statistical analysis using independent tests sample t-test, one-way ANOVA, and Duncan's follow-up test. The research results show that curriculum changes have had a better effect on participants' ability to produce scientific papers.